Daily Temporal Dynamics of a Large Mammal Predator-Prey System - Vander Vennen, Lucas (University of Guelph, 2014)
Predation is a strong determinant of predator and prey behaviour, but little is known about diel predator-prey dynamics. Here I use GPS telemtry to evaluate drivers of wolf (Canis lupus) and moose (Alces alces) daily activity patterns in northern Ontario and examine how these patterns drive diel predation patterns during winter. Wolves and moose reduced velocity in warm periods of summer days, but showed little response to winter temperature. Both species increased velocity near dawn and dusk and tracked the timing of these periods throughout the year. Velocity of both wolves and moose increased kill rates of moose via encounter rate and prey detectability respectively. Crepuscular light had a negative influence on kill rate, contrary to previous hypotheses. This work shows how variation in movement parameters can provide novel insight into determinants of predator and prey activity patterns and in turn how these behaviours influence diel variation in predation. Forest Ecosystem Science Cooperative Inc. Natural Sciences and Engineering Research Council of Canada Canadian Forest Service Ontario Ministry of Natural Resources